Epitaxial growth of tin ferrite thin films using pulsed laser deposition technique - Gupta, R. K.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2011)
Epitaxial thin films of tin ferrite (SnFe(2)O(4)) were deposited on (0 0 2) oriented strontium titanate (SrTiO(3)) substrate using pulsed laser deposition method. The quality and epitaxial nature of the films were investigated by X-ray diffraction technique. The phi scan of the film and the substrate shows four folds symmetry indicating cube-on-cube epitaxial growth of the film on the substrate. The optical bandgap of the film was estimated to be 2.6 eV using optical transmittance data. Magnetic measurements indicate that the coercive field and remnant magnetization of the film decrease with increase in temperature. The presence of hysteresis loop in M vs. H plot at room temperature indicates the ferromagnetic nature of the film. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Epitaxial thin films; SnFe(2)O(4); Pulse laser deposition; Ferromagnetic; Bandgap